Profil Pembelajaran Biologi Di SMA Kabupaten Jeneponto - Rahmat Saleh; Filawati (Jurnal Indragiri Penelitian Multidisiplin, 2023)
This study aims to find out the Biology learning profiles of SMA Kab. Jeneponto. This research is a qualitative research with a survey method. Data collection was carried out using a questionnaire instrument. Respondents in this study were high school biology teachers in Kab. Jeneponto. Data were analyzed descriptive . The results of the study showed that in the implementation of learning, Biology teachers at SMA Kab. Jeneponto always prepares learning plans consisting of teaching materials (83.33%), syllabus (75%), lesson plans (95.83%), learning media (62.5%), worksheets (45.83%), evaluation sheets students (70.83%), and student observation sheets (50%). Regarding critical thinking skills, 79.16% of biology teachers are familiar with the concept of critical thinking, 75% of teachers practice critical thinking skills in learning, and 45.83 use learning models in empowering critical thinking skills. In general, high school biology teachers in Kab. Jeneponto develops learning tools and empowers students' critical thinking skills in learning.